Molecular-Scale Manipulation of Layer Sequence in Heteroassembled Nanosheet Films toward Oxygen Evolution Electrocatalysts - He, Yuanqing; Jia, Lulu; Lu, Xueyi; Wang, Chenhui; Liu, Xiaohe; Chen, Gen; Wu, Dan; Wen, Zuxin; Zhang, Ning; Yamauchi, Yusuke; Sasaki, Takayoshi; Ma, Renzhi (ACS nano, 2022)
Flocculation or restacking of different kinds of two-dimensional (2D) nanosheets into heterostructure nanocomposites is of interest for the development of high-performance electrode materials and catalysts. However, lacking a molecular-scale control on the layer sequence hinders enhancement of electrochemical activity. Herein, we conducted electrostatic layer-by-layer (LbL) assembly, employing oxide nanosheets (e.g., MnO2, RuO2.1, reduced graphene oxide (rGO)) and layered double hydroxide (LDH) nanosheets (e.g., NiFe-based LDH) to explore a series of mono- and bilayer films with various combinations of nanosheets and sequences toward oxygen evolution reaction (OER). The highest OER activity was attained in bilayer films of electrically conductive RuO2.1 nanosheets underlying catalytically active NiFe LDH nanosheets with mixed octahedral/tetrahedral coordination (NiFe LDHTd/Oh). At an overpotential of 300 mV, the RuO2.1/NiFe LDHTd/Oh film exhibited an electrochemical surface area (ECSA) normalized current density of 2.51 mA cm–2 ECSA and a mass activity of 3610 A g–1, which was, respectively, 2 and 5 times higher than that of flocculated RuO2.1/NiFe LDHTd/Oh aggregates with a random appearance of a surface layer. First-principles density functional theory calculations and COMSOL Multiphysics simulations further revealed that the improved catalytic performance was ascribed to a substantial electronic coupling effect in the heterostructure, in which electrons are transferred from exposed NiFe LDHTd/Oh nanosheets to underneath RuO2.1. The study provides insight into the rational control and manipulation of redox-active surface layers and conductive underlying layers in heteroassembled nanosheet films at molecular-scale precision for efficient electrocatalysis.